Strategi Pemasaran Digital dalam Meningkatkan Daya Saing UMKM Queta Foods - Erna Liswan; Laura Lahindah (Publikasi Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy with a contribution of 60% to the Gross Domestic Product and absorb 97% of the workforce. This research aims to analyze effective digital marketing strategies to increase the competitiveness of Queta Foods MSMEs in Padang City. The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation of nine informants consisting of business owners, employees, consumers, digital marketing experts, and government representatives. Data analysis uses the Miles and Huberman model with source triangulation to ensure the validity of the data. The results show that the most effective digital marketing strategy is a combination of a multichannel approach through Instagram, TikTok, and WhatsApp Business with authentic content that highlights Minang cultural values. The main obstacles faced include limited digital literacy, human resources, time, and content production equipment internally, as well as technical disruptions and fierce competition externally. Information technology acts as a digital infrastructure that enables efficient communication, transactions, and data-driven decision-making. This research recommends the formation of an internal digital team, investment in content support equipment, and the use of training programs from the government to increase the digital capacity of MSMEs.